AN IMPLEMENTATION OF DUOLINGO APPLICATION FOR EXPANDING VOCABULARY IN WRITING DESCRIPTIVE TEXT TO HIGH SCHOOL STUDENTS - Rahmawati, Anisa; Hamsia, Waode; Yunianti, Sofi (TELL - US JOURNAL, 2023)
After the covid-19 pandemic, everything was online, including learning. Teachers no longer have to always race on books in the learning process, they can take advantage of technology that is smartphones. Therefore, the aim of this study is to find out how Duolingo application is implemented on 10th grade’ students along with the students’ response. Duolingo itself is a learning app that has the highest rating in the education field on the Appstore. This application provides various features and also integrated skills such as 4 skills (reading, writing, listening, and speaking), then pronunciation, vocabulary, and grammar. Since the previous study was only discussed vocabulary, the writer conducts writing skill for this study. Through this application, teachers will be easier to introduce various vocabulary for students to write descriptive text. In addition, students also become more interested in learning English and the learning process in the classroom is not boring anymore. This study analyzed teaching and learning process using descriptive qualitative method with 3 instruments those were observation, questionnaire and interview. It is stated that, based on the result of observation was the students became very enthusiastic and excited in the learning process of writing descriptive text in the classroom. Besides that, it is stated from the results of the questionnaire could be concluded that the students felt helping by the Duolingo application for learning vocabulary in writing descriptive text, and this application was also easily accessible.